2020
DOI: 10.1089/aut.2019.0058
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Autism in Young Adulthood: Applying Social Network Methods to Measure the Social Capital of Autistic Young Adults

Abstract: Social isolation is a core challenge associated with autism. Interpersonal relationships and the resources and support embedded in the social networks of autistic young adults could impact key adult outcomes, including quality of life, mental health, employment, and independence. However, little research systematically measures the networks of autistic young adults and network impact on key adult outcomes. This article demonstrates how social network analysis can be adapted for the field of autism to measure y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…One review article noted that under‐represented study participants included autistic individuals who were women, transgender, non‐White, low income, and those with intellectual disability or with minimal speaking communication (McGhee Hassrick et al, 2021). Nine studies utilized self‐reported responses of autistic individuals (Fernandes et al, 2021; Hotez et al, 2022; McGhee Hassrick et al, 2020; Song, Nonnemacher, Miller, Anderson, & Shea, 2022; Song, Salzer, Nonnemacher, Miller, & Shea, 2022; Song, Salzer, Nonnemacher, & Shea, 2022; Sosnowy et al, 2018; Sosnowy et al, 2019; Steinberg et al, 2022). Six articles included autistic co‐authors on the writing team (Lord et al, 2022; Roux et al, 2019; Roux, Rast, Anderson, et al, 2020; Roux, Rast, Garfield, et al, 2020; Shattuck et al, 2020; Steinberg et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One review article noted that under‐represented study participants included autistic individuals who were women, transgender, non‐White, low income, and those with intellectual disability or with minimal speaking communication (McGhee Hassrick et al, 2021). Nine studies utilized self‐reported responses of autistic individuals (Fernandes et al, 2021; Hotez et al, 2022; McGhee Hassrick et al, 2020; Song, Nonnemacher, Miller, Anderson, & Shea, 2022; Song, Salzer, Nonnemacher, Miller, & Shea, 2022; Song, Salzer, Nonnemacher, & Shea, 2022; Sosnowy et al, 2018; Sosnowy et al, 2019; Steinberg et al, 2022). Six articles included autistic co‐authors on the writing team (Lord et al, 2022; Roux et al, 2019; Roux, Rast, Anderson, et al, 2020; Roux, Rast, Garfield, et al, 2020; Shattuck et al, 2020; Steinberg et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, across topical domains, studies were lacking in inclusion of autistic participants, a focus on equity, or use of multisectoral data. However, studies pioneered advances in the measurement of gender identity (Steinberg et al, 2022), sexual and reproductive health (Graham Holmes et al, 2020), community participation (Song, Nonnemacher, Miller, Anderson, & Shea, 2022; Song, Salzer, Nonnemacher, Miller, & Shea, 2022) and social networks (Hassrick et al, 2018; McGhee Hassrick et al, 2020).…”
Section: Resultsmentioning
confidence: 99%